(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The analysis of normatively – legal acts of adjusting of registration politics of enterprise is conducted in the article. The article is devoted to theoretical substantiation of certain critical accounting policies, investigated the nature and purpose of accounting policies. It is proved that the accounting policy is developed individually by each enterprise and is designed to ensure the reliability and accuracy of their financial information system. Therowoffactorsofinfluenceiscertainonachoiceandgroundofregistrationpolitics. The stages of construction of registration politics are worked out. It is educed that in labours of home and foreign scientists large attention is spared to the aspects of registration politics: methodical, technical and organizational. Development and claim of registration politics are the important stage during creation of any enterprise, on the skill fully formed registration politics efficiency of management of enterprise economic activity and strategy of his development depend on the protracted prospect.